Effects of habitat patch size and isolation on the population structure of two siphonarian limpets - Johnson, Linda Gail (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
Habitat fragmentation is a fundamental process that determines trends and patterns of distribution and density of organisms. These patterns and trends have been the focus of numerous terrestrial and marine studies and have led to the development of several explanatory hypotheses. Systems and organisms are dynamic and no single hypothesis has adequately accounted for these observed trends. It is therefore important to understand the interaction of these processes and patterns to explain the mechanisms controlling population dynamics. The main aim of this thesis was to test the effect of patch size and isolation on organisms with different modes of dispersal. Mode of dispersal has previously been examined as a factor influencing the effects that habitat fragmentation has on organisms. Very few studies have, however, examined the mode of dispersal of marine organisms because it has long been assumed that marine animals are not directly influenced by habitat fragmentation because of large-scale dispersal. I used two co-occurring species of siphonariid limpets with different modes of dispersal to highlight that not only are marine organisms affected by habitat fragmentation but that they are affected in different ways. The two species of limpet, Siphonaria serrata and Siphonaria concinna, are found within the same habitat and have the same geographic range along the South African coastline, however, they have different modes of dispersal and development. The effect of patch size on organism density has been examined to a great extent with varied results. This study investigated whether habitat patch size played a key role in determining population density and limpet body sizes. The two species are found on the eastern and southern coasts of South Africa were examined across this entire biogeographic range. Patch size was found to have a significant effect on population density of the pelagic developer, S. concinna, but not the direct developing S. serrata. Patch size did play a role in determining limpet body size for both species. S. concinna body size was proposed to be effected directly by patch size whilst S. serrata body size was proposed to be affected indirectly by the effects of the S. concinna densities. The same patterns and trends were observed at five of the seven examined regions across the biogeographic range. The trends observed for S. concinna with respect to patch size conform to the source-sink hypothesis with large habitat patches acting as the source populations whilst the small habitat patches acted as the sink populations. Many previous studies have focused on the effects of habitat patch size at one point in time or over one season. I tested the influence of habitat patch size on the two species of limpets over a period of twelve months to determine whether the trends observed were consistent over time or whether populations varied with time. S. concinna showed a consistently significant difference between small and large patches; whilst S. serrata did not follow a consistent pattern. The mode of dispersal for the two limpets was used to explain the different trends shown by the two species. This examination allowed for the determining of source and sink populations for S. concinna through the examination of fluctuations in limpet body sizes and population densities at small and large habitat patches over twelve months. The direct developing S. serrata trends could not be explained using source-sink theory, as populations were independent from one another. S. serrata demonstrated body size differences at small and large patches which, may be explained by interspecific and intraspecific competition. Habitat isolation is known to play an important role in determining the structure of assemblages and the densities of populations. In this study the population density of the pelagic developing S. concinna showed a weak influence of degree of isolation whilst that of the direct developing S. serrata did not, which may be because of habitat patches along the South African coastline not having great enough degrees of isolation. The population size-structure was influenced directly influenced by isolation for S. concinna, whilst the different population size structure for S. serrata may be explained by assemblage co-dependence. The mode of dispersal showed effects on the relationship of population density and population size-structure with habitat size and isolation. This study indicates the importance of investigating patterns and processes across a range of spatial and temporal scales to gain a comprehensive understanding of factors effecting intertidal organisms.
Keywords: Siphonaria; Limpets; Population biology; Marine ecology; Habitat selection; Animals -- Dispersal; Ecological heterogeneity; Animal populations; Biodiversity